APPLICATION OF DIGITAL PRODUCTION MODELS IN PRACTICE - Kurbanov Ma'murjon Gayrat Ogli (Galaxy International Interdisciplinary Research Journal, 2023)
Today, digitization is an integral part of the modern world. It is becoming increasingly clear that all manufacturing and service sectors in developed countries will not be able to remain competitive and deliver products and services that must be ready on time and on schedule without modern technology. For this reason, this article aims to develop a conceptual system that implements the effectiveness of digital tools for the introduction of a circular economy in railway and construction enterprises.